Medical genetics and the Human Genome Project: a historical review - Haq, M M (Texas medicine, 1993)
The $3 billion, 15-year international project to map out the nucleotide sequence of the entire human genome could revolutionize medical care in the 21st century. The location, makeup, and function of the 50,000 to 100,000 human genes could lead to tailor-made therapies not only for treating diseases but for preventing them. There may be a major role for the genetic engineer in the practice of medicine. On the other hand, the technology could identify people with undesirable genetic profiles who may be subject to discrimination by insurance companies, employers, and others. Physicians who fail to perform genetic screening may face malpractice suits for wrongful births. This article traces the historical evolution of our knowledge regarding medical genetics from the Talmud to the present day.